Ferulic acid inhibits lipogenesis and ameliorates MASLD via targeting PGC-1β - Cui, Kaili; Ren, Laifeng; Zhang, Lichao; An, Yuxuan; Ji, Pengyu; Yang, Ye; Li, Feng; Li, Zhuoyu (Frontiers in Nutrition, 2026)
IntroductionMetabolic dysfunction-associated steatotic liver disease (MASLD) is characterized by hepatic steatosis and increased triglyceride content. Thus, intervention in fatty acid metabolism is very desirable for NAFLD treatment. Ferulic acid (FA) is a plant-derived bioactive molecule that regulates lipid metabolism.MethodsHigh-fat diet (HFD)-fed mice and free fatty acid (FFA) -treated cells were used to evaluate the improvement of FA. The target proteins of FA were screened by solid phase extraction combined with mass spectrometry.ResultsIt was found that FA effectively improved MASLD in vivo and in vitro. Interestingly, PPAR gamma-coactivator-1beta (Ppargc1β, also known as PGC-1β) was the target of FA intervention in MASLD. FA directly bound to PGC-1β and inhibited its expression through the ubiquitin-proteasome pathway. Furthermore, Overexpression of PGC-1β abolished the ameliorative effect of FA on MASLD. In addition, FA inhibited lipogenesis through the PGC-1β/SREBP1 axis, thereby improving MASLD.DiscussionThis work uncovered a novel plant-derived therapeutic strategy targeting a previously unrecognized PGC-1β/SREBP1 mechanism in MASLD.